2020
DOI: 10.3390/vaccines8030461
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Modulations by Products of the Gut Microbiota

Abstract: The gut microbiota, which consists of all bacteria, viruses, fungus, and protozoa living in the intestine, and the immune system have co-evolved in a symbiotic relationship since the origin of the immune system. The bacterial community forming the microbiota plays an important role in the regulation of multiple aspects of the immune system. This regulation depends, among other things, on the production of a variety of metabolites by the microbiota. These metabolites range from small molecules to large macro-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 97 publications
0
21
0
Order By: Relevance
“…Other functions of SCFA include activating and facilitating migration of DC cells at sites of inflammation and infection. Activated DC cells as described earlier, are vital as an antiviral defense mechanism by releasing IFN in COVID-19 sepsis [52,53,61,62]. SCFA activities also effect cell metabolism and may also inhibit transcription of genes by inhibiting histone deacetylase (HDAC) activity [63].…”
Section: Complex Interaction Between Microbiota Ace-2 Expression and Vitamin D In Covid Pathogenesismentioning
confidence: 94%
See 3 more Smart Citations
“…Other functions of SCFA include activating and facilitating migration of DC cells at sites of inflammation and infection. Activated DC cells as described earlier, are vital as an antiviral defense mechanism by releasing IFN in COVID-19 sepsis [52,53,61,62]. SCFA activities also effect cell metabolism and may also inhibit transcription of genes by inhibiting histone deacetylase (HDAC) activity [63].…”
Section: Complex Interaction Between Microbiota Ace-2 Expression and Vitamin D In Covid Pathogenesismentioning
confidence: 94%
“…One such group of molecules is short-chain fatty acids (SCFAs)-such as butyrate, propionic acid and acetic acid. These are produced by microbial fermentation of undigested or partially digested dietary fiber and have broad effects on epithelial barrier and host immune system function [8,61]. It promotes production of mucus, secretion of secretory IgA to enhance local immunity.…”
Section: Complex Interaction Between Microbiota Ace-2 Expression and Vitamin D In Covid Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The change in the microbiota environment may result in downregulation of immune system function. 4 Recent studies have demonstrated that cerebral ischemic injury induces changes of intestinal flora and becomes worse under nervous inflammation. 5 However, it is not clear how intestinal flora regulate the brain-gut axis.…”
mentioning
confidence: 99%